KESULITAN ANAK SELAMA BELAJAR DARI RUMAH (BDR) DAN PENGENALAN ENGLISH CLUB - Nadia, Fatma; Panama Rahdja , Dika Rosti (Inspiratif Pendidikan, 2022)
It has been almost a year since Covid-19 has become a world pandemic, since it was announced by the World Health Organization (WHO) on March 11, 2020. The Indonesian government even issued a Large-Scale Social Restriction (PSBB) regulation to minimize the spread of Covid-19 and its effects. PSBB is applied in all sectors of life, including the education sector. Large-scale social restrictions in the education sector are carried out by the government through the Ministry of Education and Culture by issuing Guidelines for the Implementation of Home Learning, known as BDR. The purpose of this study was to find out the various difficulties experienced by early childhood during the BDR period in the Covid-19 Era. So that effective solutions can be obtained or produced to minimize the difficulties of implementing Learning from Home so that the objectives of National Education can be achieved. English club activities are a solution to overcome the boredom experienced by children during BDR. The results showed that there were many difficulties in implementing Learning from Home. Even so, we can still find various solutions to overcome the difficulties that arise from holding BDR. In addition, the cooperation of all parties involved in educational activities, namely, teachers, parents and students as well as the Ministry of Education and Culture is the key in overcoming existing difficulties.